Ancient Christian care for prisoners: first and second centuries - T. Nicklas (Acta Theologica)
This study deals with the question as to whether first- and second-century sources reflect ancient Christian practices of care for prisoners and in how far these sources help clarify the reasons why Christians cared for prisoners in different contexts. The study explores material not only from the New Testament Gospels (Matt. 25; Luke 4) and Acts, but also from the Pauline Corpus and extra-canonical literature such as Ignatius of Antioch’s Epistles, later Acts of the Apostles, Martyrdom literature and even a passage from Lucian of Samosata’s Life of Peregrinus. The article concludes that the evidence for Christian care for prisoners is earlier and more widespread than usually assumed. While some sources do not reflect on reasons for this practice, others put it into wider horizons: Matthew links care for prisoners with the notion that actions toward people in need are actions toward Christ, the judge himself – an innovative view that is certainly tied to the special circumstances of early Christians. Luke, however, borrows Isaianic motifs, linking freedom for captives with the Messianic Age.